Revitalisasi Keilmuan Fakultas Ushuluddin Menghadapi Tantangan Peradaban Global - Nasihun Amin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2014)
Abstract: The wave of information and communication appear to cause global clash of civilization. This seriously challenges religion because morality lies as the basic problem. Concerning this issue, Ushuluddin faculty, that produces religious scholars, has a strategic position in responding to this situation. As an academic institution, Ushuluddin faculty has to do self-reformulation and revitalization in order to respond the global challenge. It does not only focus on producing scholars that are excellent in understanding religious studies (substantial skill). But, it has also to equip them with great skill on technicality, practicalities as well as relational skill. These expertise and skills will give them authority to direct morality in this global civilization. Abstrak: Adanya gelombang informasi dan komunikasi ternyata membawa dampak benturan peradaban pada skala global. Pada keadaan demikian, agama mendapat tantangan yang luar biasa berat karena inti persoalannya adalah pada moral. Dalam konteks ini, peran Fakultas Ushuluddin (FU) sebagai pencetak ahli agama sebagai bagian penting dalam institusi agama, mempunyai posisi yang strategis. Karenanya, tuntutan yang harus segera dilakukan adalah bagaimana FU melakukan reformulasi dan revitalisasi dalam dirinya untuk menjawab tantangan global tersebut. Melalui penguasaan dan pemahaman agama yang baik dan tepat (substantial skill), yang didukung kecakapan teknis (technical skill) tertentu dan kecakapan relasional (relational skill), maka mereka akan memiliki wibawa moral untuk memberikan arah moral dalam peradaban global.